Improved Agilla Middleware Architecture to Increase the Efficiency of Wireless Sensor Networks - V P, Ms Priyanka; Pramilarani, Ms K. (IJRDO -Journal of Computer Science Engineering, 2016)
Wireless Sensor Network (WSN) consists of number of sensor nodes which communicate with each through sensors, where each node consists of sensor, processor and memory. The main aim of wireless sensor network is to reduce the energy consumption and increase speed. For the design and implementation of wireless sensor networks middleware technology Agilla is used. In three tier client server architecture middle tier is called as middleware and is placed between client and server. Middleware help to bridge the gap between high level application and under the control of the operations of Wireless Sensor Networks. Agilla is mobile agent based middleware run on TinyOS. Application programs are composed of agents, which be transmitted across the nodes. Each node could support multiple autonomous agents and maintains a neighbour list and tuple space. The agents are transmitted to build an application by following neighbour list. With multiple autonomous agents, it allows multiple users from different applications share the network simultaneously. Agilla has good performance on reliability